1985
DOI: 10.1128/aac.28.2.354
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of trimethoprim resistance in fecal flora

Abstract: The emergence of trimethoprim (TMP) resistance in fecal flora was compared in patients with urinary tract infection treated with TMP or TMP-sulfamethoxazole. No significant differences were found in the occurrence of TMP-resistant fecal aerobic bacteria in the two treatment groups before and after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Heavy gastrointestinal colonization of TMP-resistant bacteria during TMP or TMPsulfonamide treatment has been shown to occur during travel for 2 weeks in Mexico (59,60). Although TMP has also been widely used in Finland, gastrointestinal colonization of TMP-resistant strains was not found after 10 days of treatment of urinary tract infections with TMP or a TMPsulfonamide combination (42). This difference might be explained by a more extensive, less restricted consumption of TMP in Mexico (42; S. Levy, Letter, N. Engl.…”
Section: Spread Of Tmp Resistancementioning
confidence: 98%
“…Heavy gastrointestinal colonization of TMP-resistant bacteria during TMP or TMPsulfonamide treatment has been shown to occur during travel for 2 weeks in Mexico (59,60). Although TMP has also been widely used in Finland, gastrointestinal colonization of TMP-resistant strains was not found after 10 days of treatment of urinary tract infections with TMP or a TMPsulfonamide combination (42). This difference might be explained by a more extensive, less restricted consumption of TMP in Mexico (42; S. Levy, Letter, N. Engl.…”
Section: Spread Of Tmp Resistancementioning
confidence: 98%
“…This study design has been used to compare selection of drug-resistant bacteria from the fecal flora by trimethoprim alone versus trimethoprim-sulfamethoxazole (table 6). Collectively, these studies do not provide convincing evidence that trimethoprim alone is more likely to select resistant bacteria than is the combination [53][54][55][56]. However, 3 of the 4 studies showed selection of drug- Seppala et al [40] Studies at the population level not showing an association between prescribing and resistance Three regions of Finland Gram-negative bacteria; urinary isolates; trimethoprim resistance No clear correlation between the use of trimethoprim and the level of resistance was found.…”
Section: Studies Based On Linking Data About Clinical Cultures and Anmentioning
confidence: 99%
“…SUL alone is ineffective against enterococci (70). Until more evidence is accumulated, TMPSULs or TMP alone should not be used as a first-line drug in the treatment of enterococcal urinary tract infections (107).…”
Section: Spread Of Tmp and Sul Resistancementioning
confidence: 99%